Daily field checking list by Walter Rosene, April 5, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Little Wall Lake by Walter Rosene and Walter Rosene, Jr., April 5, 1936. Also notes the lake was frozen over except for a very few open spots where the Waterfowl were concentrated. Plustek--flatbed